EDITORIAL - Montenegro, Iván Ricardo Miranda (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The complex field of learning and teaching a second/foreign language is always presenting the challenge of theoretically going forwards and backwards in the search of the best chances for doing our job more effective. People are different and so are settings, this is the main reason which opens the scope for languages teachers to reflect and propose alternatives for those varieties of learners learning in diverse spacesaround the world.